BUILDING LEARNERS’ CHARACTER THROUGH THE TRADITIONAL DANCE PERFORMANCE OF MINANGKABAU - Indrayuda Indrayuda (International Conference on Languages and Arts, 2014)
This article aims to explain and reveal the character building activities for learners through an appreciation of dance performances. Dance as an expression of human being capable of expressing various moral messages through symbols of movement, music, and costumes and properties, so that they can be said for character education media. Nowadays, almost complete degradation symptoms character on learners in schools in West Sumatra. Low understanding and experience of character for learners as cultured human and social beings, who live in the area which is known with indigenous philosophy and culture, such as Minangkabau with the philosophy of "adat basandi Syarak, Syarak basandi kitabbullah". In fact, many students who do not behave according to the characters of Minangkabau. This fact affects the social stability and social integration in the learning process in West Sumatra. Therefore, one way to solve this problem is to provide an understanding of the character of Minangkabau  through  Minangkabau dance performances, which are considered to have substance on the characteristics of Minangkabau.   Keywords: Character, Dance Arts Performing, and Students.